2014
DOI: 10.1093/hsw/hlu029
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Health Correlates of Adverse Childhood Experiences among Low-Income Women

Abstract: The present study used secondary data gathered from a statewide random sample of 1,073 adult women enrolled in Utah's single-parent cash assistance program and logistic regression to examine associations between self-reported physical, emotional, and sexual abuse during childhood and later life physical and mental health indicators. Results demonstrated significant associations between low-income women's self-reports of physical, emotional, or sexual abuse in childhood, and current and lifetime anxiety disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…The above research is supported and correlates with various other studies which report that survivors of childhood sexual abuse are at risk of depression, feelings of guilt, decrease in selfworth, apathy, a decrease in moral judgment, substance abuse and the development of mental disorders (Singh et al, 2014;Van Rensburg & Barnard, 2005;Raabe et al, 2015). According to Cambron, Gringeri and Vogel-Ferguson (2014) There appears to be a serious need, therefore, to devise a novel strategy to help survivors of sexual abuse to deal with the accompanying trauma. Using a narrative approach towards the co-constructing of new identities and life stories (where the person is seen as the expert), career counsellors can potentially provide a useful and functional strategy in their quest for finding ways in which to promote a sense of career resilience and resilience in general among survivors of sexual abuse.…”
Section: The Long-term Effects Of Sexual Abusesupporting
confidence: 76%
See 1 more Smart Citation
“…The above research is supported and correlates with various other studies which report that survivors of childhood sexual abuse are at risk of depression, feelings of guilt, decrease in selfworth, apathy, a decrease in moral judgment, substance abuse and the development of mental disorders (Singh et al, 2014;Van Rensburg & Barnard, 2005;Raabe et al, 2015). According to Cambron, Gringeri and Vogel-Ferguson (2014) There appears to be a serious need, therefore, to devise a novel strategy to help survivors of sexual abuse to deal with the accompanying trauma. Using a narrative approach towards the co-constructing of new identities and life stories (where the person is seen as the expert), career counsellors can potentially provide a useful and functional strategy in their quest for finding ways in which to promote a sense of career resilience and resilience in general among survivors of sexual abuse.…”
Section: The Long-term Effects Of Sexual Abusesupporting
confidence: 76%
“…Resiliency scale subscales In a study involving 1073 adult woman and survivors of CSA, Cambron et al (2014) posit that childhood sexual abuse will not only have a detrimental long-term impact on the quality of interpersonal relationships, but also cause difficulty in forming healthy relationships. My findings above seem to confirm and extend the above results and would appear to predict a possible negative impact on Suzi"s future career resilience.…”
Section: Resiliency Scale Subscalesmentioning
confidence: 99%
“…Previous research among low-income women has demonstrated high rates of childhood violence and abuse that have been associated with poor physical and mental health during adulthood (Cambron et al, 2014;Gringeri & Vogel-Ferguson, 2012;Harris & Vogel-Ferguson, 2007); results show a strong dose -response relationship between ACEs and anxiety disorder and PTSD. Given the increased likelihood of depression among low-income women and the decreased likelihood of obtaining employment among low-income women suffering from mental illness Jayakody & Stauffer, 2000), this study employs childhood abuse as a predictor of depression.…”
Section: Research Questionmentioning
confidence: 85%
“…Recent research has highlighted an extensive history of childhood abuse among low-income women in Utah (Cambron, Gringeri, & Vogel-Ferguson, 2014;Gringeri & Vogel-Ferguson, 2012). Data collected by state agencies in conjunction with in-person interviews have provided insight into the current and historical life circumstances of women accessing public assistance in Utah.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation